Identification and α-Glucosidase Inhibitory Activity of Meroterpenoids from Hericium erinaceus - Chen, Baosong; Han, Junjie; Bao, Li; Wang, Wenzhao; Ma, Ke; Liu, Hongwei (Planta Medica, 2020)
Hericium erinaceus is a very popular edible and medicinal mushroom used for the treatment of enervation and gastrointestinal diseases in Eastern Asia. Chemical investigation on the fruiting body of Hericium erinaceus led to the isolation of 4 new (1 – 4) and 10 known meroterpenoids (5 – 14). The structures of new compounds were determined via analysis of NMR and MS data in combination with chemical derivatization. The inhibitory activities of 1 – 14 against α-glucosidase were evaluated using p-nitrophenyl-α-D-glucopyranoside, sucrose, or maltose as substrate. Compounds 6, 9, 11 – 13 were demonstrated to show the α-glucosidase inhibitory activities. This work confirms the potential of H. erinaceus in the treatment of diabetes.
Keywords: Hericium erinaceus; Hericiaceae; meroterpenoid; α-glucosidase inhibition